2018
DOI: 10.2147/sccaa.s151763
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells as nuclear donors improve viability and health of cloned horses

Abstract: IntroductionCell plasticity is crucial in cloning to allow an efficient nuclear reprogramming and healthy offspring. Hence, cells with high plasticity, such as multipotent mesenchymal stem cells (MSCs), may be a promising alternative for horse cloning. In this study, we evaluated the use of bone marrow-MSCs (BM-MSCs) as nuclear donors in horse cloning, and we compared the in vitro and in vivo embryo development with respect to fibroblasts.Materials and methodsZona-free nuclear transfer was performed using BM-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…Somatic cell nuclear transfer and embryo transfer were performed as previously described by Olivera et al [35, 36]. Briefly, equine oocytes were in vitro matured and enucleated by micromanipulation.…”
Section: Methodsmentioning
confidence: 99%
“…Somatic cell nuclear transfer and embryo transfer were performed as previously described by Olivera et al [35, 36]. Briefly, equine oocytes were in vitro matured and enucleated by micromanipulation.…”
Section: Methodsmentioning
confidence: 99%
“…Then, in addition to the low blastocyst rates reported for horse cloning, this factor might explain the lower embryo developmental rate of the edited cloned embryos compared to controls. To increase horse cloning development, MSCs could be used as nuclear donors 1 . However, it was demonstrated that MSCs undergo senescence at early passages, showing alterations in cellular morphology, telomere shortening and proliferation arrest after 30 population doublings or 7-10 passages 53 , which makes the generation of edited clonal cell lines rather difficult.…”
Section: Discussionmentioning
confidence: 99%
“…597, Río Cuarto, Córdoba, Argentina, ZIP code: 5805) and oocytes were matured for 24 h. Matured oocytes were then treated with pronase (#P-8811, Sigma Aldrich Co., USA) to remove the zona pellucida, enucleated by micromanipulation and electrically fused with a donor cell (wild type fibroblast, G1-1 µg-C23, G2-5 µg-C13 or G2-1 µg-C02 cell). In order to incorporate a positive control, we performed the same procedure using MSCs (with the same genomic background as the HFFs) as nuclear donors, considering the enhanced effectiveness of using this type of cells in horse cloning 1 . After 2.5 h fusion, reconstructed embryos were activated with 8.7 μM ionomycin (#I24222; Invitrogen, CA, USA) for 4 min followed by individual culture in a combination of 1 mM 6-dimethylaminopurine (6-DMAP; # D2629, Sigma Aldrich Co., MO, USA) and 5 mg/ml cycloheximide (CHX; #C7698, Sigma Aldrich Co., MO, USA) in 5 µl drops of DMEM/F12 (#D8062, Gibco, Grand Island, NY, USA) for 4 h. Reconstructed embryos were cultured in DMEM/F12 containing 10% FBS, and 1% penicillin-streptomycin in the Well-of-the-Well system, three embryos together per well.…”
Section: Methods Grnas Design and Construction Two Grnas Complementamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, work from Argentina has suggested that use of bone‐marrow derived mesenchymal stem cells as donor cells for nuclear transfer may increase the likelihood of production of normally healthy foals (Olivera et al., , ). The possibility exists that cloning could be performed using somatic cells isolated from frozen‐thawed semen, which would allow production of clones in cases in which frozen semen was the only existing source of cells from an individual.…”
Section: Cloning (Nuclear Transfer)mentioning
confidence: 99%